HOTS Performance Based Assessment to improve Critical Thinking Skills in Speaking Class at ANNIDA Senior High School - Afifah, Early Suryani; Widyantoro, Agus (International journal of multicultural and multireligious understanding, 2025)
This research investigates the effectiveness of higher order thinking skills (HOTS) through performance-based assessment (PBA) to improve speaking skills. This research used classroom action research (CAR) conducted in two cycles. The subjects were 20 students of grade XI. The research instruments used observation sheets, tests, and questionnaires. The pre-test results showed that only 20% of students met the KKM, increasing to 45% in Cycle 1 and 55% in the post-test. However, further enhancement was needed to reach the 80% success criterion, prompting Cycle 2. The implementation of HOTS through PBA can improve students' speaking ability, indicated by better performance in fluency, vocabulary, pronunciation, and grammar. The questionnaire results also showed positive student responses, indicating that HOTS through PBA can increase motivation, confidence, and learning interest. Based on these findings, it can be concluded that the application of HOTS through PBA can be an effective alternative to improve speaking skills, as well as encourage students to think critically, creatively, and communicatively.